Conversion and integration into green infrastructure of former industrial urban quarter: theoretical model and experimental design solutions - Žmėjauskaitė, Diana; Grazuleviciute-Vileniske, Indre (Landscape Architecture and Art, 2024)
The regeneration of former industrial sites has become increasingly relevant in the context of urban regeneration and sustainable urban development in general. Industrial structures in urban environments, shaped by the socioeconomic conditions of their time, often fall into disuse, posing significant challenges for urban planners and developers. Such neglected sites not only deteriorate physically but also fragment urban areas, disrupting social and ecological networks. This research raises the hypothesis that by converting abandoned industrial areas into ecologically integrated urban spaces, cities can enhance public access to nature, reduce their environmental footprint, and revitalize fragmented neighborhoods. The paper includes the analysis of relevant literature on the topics of urban regeneration, building conversion, and green infrastructure, existing conversion projects, and proposes a theoretical model that guides the transformation of former industrial sites into viable, sustainable urban spaces. The formulated theoretical model was applied to experimental design of a former industrial site in Kaunas (Lithuania). The findings of the research emphasize the significance of re-establishing human interaction with nature through adaptive reuse and underline the potential social, economic, and ecological benefits of integrating formerly abandoned areas into the urban fabric.